Effects of Mn and Cu Edoping on the microstructures and optical properties of sol-gel derived ZnO thin films - Bahsi, Z. Banu; Oral, A. Yavuz (Elsevier, 2007)
Both doped (Cu or Mn) and undoped zinc oxide thin films were deposited on glass substrates by a sol-gel technique. Zinc acetate, copper acetate and manganese nitrate were used as metal sources. A homogeneous and stable solution was prepared by dissolving ZnO acetate (ZnAc) in the solution of 2-propanol and ethanolamine (EA) followed by mixing with the doping solutions. ZnO:(Cu or Mn) thin films were obtained after preheating the spin coated films at 250 degrees C for 1 min after each coating. A post-annealing at 550 degrees C was applied to all films for 1 h after the deposition of the last layer. XRD analysis revealed that all films consist of single phase ZnO with zincite structure (Card no: 36-1451). While undoped films showed the strongest orientation, c-axis grain orientation was apparent in all films. TGA analysis of the undoped dried gel showed that weight loss continued until similar to 400 degrees C. Compared to the undoped film, grain size of the films decreased by Mn doping and increased by Cu doping. All films had a very smooth surface with RMS surface roughness values between 0.23 and 1.15 nm and surface roughness increased by doping. Both Mn and Cu doping resulted in a slight decrease in the optical band gap of the films. The largest width of band tail was measured in Mn-doped film. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: doped zinc oxide; sol-gel; thin film; transparent coating